2014
DOI: 10.1074/mcp.m113.033217
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Ras-related Protein Rab 5C-dependent Endocytosis and Glycolysis in Cisplatin-resistant Ovarian Cancer Cell Lines

Abstract: Drug resistance poses a major challenge to ovarian cancer treatment. Understanding mechanisms of drug resistance is important for finding new therapeutic targets. In the present work, a cisplatin-resistant ovarian cancer cell line A2780-DR was established with a resistance index of 6.64. The cellular accumulation of cisplatin was significantly reduced in A2780-DR cells as compared with A2780 cells consistent with the general character of drug resistance. Quantitative proteomic analysis identified 340 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Downregulation of vimentin was identified in widely used drug resistant ovarian cancer cell lines in the present and previous studies [14, 23], suggesting that the low expression of vimentin correlated with drug resistance in ovarian cancer cells. Silencing of vimentin expression in A2780, HO-8910-PM and HO-8910 cells resulted in markedly increase the cell resistance to cisplatin further demonstrating that vimentin mediates drug resistance in ovarian cancer cells (Figure 2(f, i), Supplementary Figure S1f).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Downregulation of vimentin was identified in widely used drug resistant ovarian cancer cell lines in the present and previous studies [14, 23], suggesting that the low expression of vimentin correlated with drug resistance in ovarian cancer cells. Silencing of vimentin expression in A2780, HO-8910-PM and HO-8910 cells resulted in markedly increase the cell resistance to cisplatin further demonstrating that vimentin mediates drug resistance in ovarian cancer cells (Figure 2(f, i), Supplementary Figure S1f).…”
Section: Discussionsupporting
confidence: 71%
“…Our previous study showed that vimentin was downregulated in drug resistant ovarian cancer cell line A2780-DR [14]. Vimentin, a member of the intermediate filament (IF) family, is ubiquitously expressed in mesenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The standard first-line treatment for EOC is primarily cytoreductive surgery (CRS) followed by platinum-based chemotherapy [3]. However, the efficacy of chemotherapy is limited, for approximately 25% of patients relapse within six months and the overall five-year survival rate is about 30% [4]. Therefore, it’s imperative to find useful clinical markers to predict chemosensitivity of cisplatin in EOC and to decrease the failure of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS/MS was performed as described previously [28] with slight modifications. Briefly, the samples were resolved using an Acclaim PepMap RSLC column on a Thermo Scientific UltiMate 3000 RSLCnano System.…”
Section: Methodsmentioning
confidence: 99%